2022
DOI: 10.2147/idr.s345855
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Polymorphism Analysis in Drug-Resistant Genes in M. tuberculosis Clinical Isolates from Western and Northern India

Abstract: Introduction The mechanistic details of first line drug (FLD) resistance have been thoroughly explored but the genetic resistance mechanisms of second line injectables, which form the backbone of the combinatorial drug resistant tuberculosis therapy, are partially identified. This study aims to highlight the genetic and spoligotypic differences in the second line drug (SLD) resistant and sensitive Mycobacterium tuberculosis ( Mtb) clinical isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…c.254_261delGTCCGCGC, identified only in a few L6 isolates, also affects the RGRP motif and causes downstream frameshift, leaving only the first few amino acid residues of the AT-hook intact. Interestingly a recent study also revealed the presence of another mutation, R85C, affecting the RGRP motif of 25 MTB isolates in India 36 .…”
Section: Discussionmentioning
confidence: 95%
“…c.254_261delGTCCGCGC, identified only in a few L6 isolates, also affects the RGRP motif and causes downstream frameshift, leaving only the first few amino acid residues of the AT-hook intact. Interestingly a recent study also revealed the presence of another mutation, R85C, affecting the RGRP motif of 25 MTB isolates in India 36 .…”
Section: Discussionmentioning
confidence: 95%